A SERS-active capillary for direct molecular trace detection in liquids. Issue 9 (1st April 2021) - Sun, Zhoutao; Kang, Chen; Fang, Xiaohui; Liu, Hongmei; Guo, Jinxin; Zhang, Xinping
Abstract : Direct molecular trace SERS detection in liquids was performed simply using a capillary without pre-functionalization. Grazing incidence and multimode interference ensure excitation and accumulation of the longitudinal Raman signal. Abstract : The development of Surface Enhanced Raman Scattering (SERS) promotes the wide application of Raman spectroscopy in chemical and biomolecular detection. SERS detection relies on analytes in close contact with the metallic surface, and therefore direct molecular trace detection in the liquid phase is difficult. In this paper, static liquid phase SERS detection was performed simply using a capillary without pre-functionalization. Gold nanoparticles (AuNPs) with an optimized size ensure localized surface plasmons in resonance with the exciting laser light. Grazing incidence and multimode interference in the capillary ensure that the longitudinal Raman signal is effectively excited and accumulated. An enhancement factor as high as 10 8 and a detection limit of 10 −9 M of crystal violet in aqueous solution have been achieved.